The Interplay of Promotional Strategies and Service Quality in Fostering Customer Loyalty: An Empirical Study of Indonesia's E-Commerce Duopoly of Tokopedia vs. Shopee - Edward Tjahyadi (Eduvest - Journal of Universal Studies, 2026)
E-commerce plays a central role in Indonesia’s digital economy, with Tokopedia and Shopee forming a dominant duopoly that shapes user behaviour. Despite rapid sector growth and heavy reliance on price-based promotions, the long-term sustainability of customer loyalty remains unclear. Existing research largely isolates promotional strategies or service-quality antecedents, yet rarely examines their interaction within an emerging-market context where consumers are highly price-sensitive but increasingly expect advanced digital service experiences. This study addresses this gap by empirically analyzing the interplay between Perceived Promotional Attractiveness (PPA), E-Service Quality (ESQ), Customer Satisfaction (CS), and Customer Loyalty (CL) across both platforms. A quantitative-explanatory design was employed by surveying active Shopee and Tokopedia users in the Jakarta Metropolitan Area. Twenty-four indicators across four constructs (PPA, ESQ, CS, CL) were assessed using PLS-SEM, supported by bootstrapping, mediation analysis, predictive evaluation, and multi-group comparison. Findings show that ESQ is the strongest and most consistent predictor of CS on both platforms (Tokopedia β = 0.894; Shopee β = 0.759, p < 0.001). Responsiveness, problem resolution, transactional security, and delivery reliability emerged as the most critical dimensions. CS significantly predicted CL, particularly on Shopee. Conversely, PPA had minimal—and in Tokopedia’s case, slightly negative—effects on CS and CL, suggesting promotions have become hygiene factors rather than differentiators. Overall, the study concludes that service quality—not promotional intensity—is the primary driver of sustainable customer loyalty in Indonesia’s e-commerce duopoly. Strengthening secure transactions, responsive support, reliable fulfillment, and high-quality user experience is essential for long-term competitive advantage.